Prevalence of Mental Disorders, Psychological Distress, and Mental Health Services Use Among Lesbian, Gay, and Bisexual Adults in the United States - Cochran, Susan D. (2003)
Recent estimates of mental health morbidity among adults reporting same-gender sexual partners suggest that lesbians, gay men, and bisexual individuals may experience excess risk for some mental disorders as compared with heterosexual individuals. However, sexual orientation has not been measured directly. Using data from a nationally representative survey of 2,917 midlife adults, the authors examined possible sexual orientation-related differences in morbidity, distress, and mental health services use. Results indicate that gay–bisexual men evidenced higher prevalence of depression, panic attacks, and psychological distress than heterosexual men. Lesbian–bisexual women showed greater prevalence of generalized anxiety disorder than heterosexual women. Services use was more frequent among those of minority sexual orientation. Findings support the existence of sexual orientation differences in patterns of morbidity and treatment use.